Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

What is the standard form of the equation of a quadratic function with roots of 4 and -1 that passes through \((1, -9)\)?

A. \(y = 1.5x^2 - 4.5x - 6\)
B. \(y = 1.5x^2 - 4.5x + 6\)
C. \(y = -1.5x^2 - 4.5x - 6\)
D. [tex]\(y = -1.5x^2 - 4.5x + 6\)[/tex]


Sagot :

To find the standard form of the quadratic equation with roots 4 and -1 that passes through the point \((1, -9)\), let's follow these steps:

### Step 1: Write the Quadratic Equation in Factored Form
Since the roots of the quadratic function are 4 and -1, we can write the quadratic function in its factored form as:
[tex]\[ y = a(x - 4)(x + 1) \][/tex]
Here, \(a\) is a constant that we need to determine.

### Step 2: Expand the Factored Form
Expand the equations \(y = a(x - 4)(x + 1)\):
[tex]\[ y = a(x^2 + x - 4x - 4) \][/tex]
[tex]\[ y = a(x^2 - 3x - 4) \][/tex]

### Step 3: Use the Given Point to Find \(a\)
We are given that the quadratic function passes through the point \((1, -9)\). This means when \(x = 1\), \(y = -9\).

Substitute \(x = 1\) and \(y = -9\) into the expanded equation:
[tex]\[ -9 = a(1^2 - 3(1) - 4) \][/tex]
Simplify inside the parentheses:
[tex]\[ -9 = a(1 - 3 - 4) \][/tex]
[tex]\[ -9 = a(-6) \][/tex]
Solve for \(a\):
[tex]\[ a = \frac{-9}{-6} \][/tex]
[tex]\[ a = \frac{3}{2} \][/tex]

### Step 4: Substitute \(a\) Back into the Quadratic Equation
Now that we have \(a = \frac{3}{2}\), we can substitute this back into the equation:
[tex]\[ y = \frac{3}{2}(x^2 - 3x - 4) \][/tex]

### Step 5: Write the Quadratic Equation in Standard Form
Distribute \(\frac{3}{2}\) to each term inside the parentheses:
[tex]\[ y = \frac{3}{2}x^2 - \frac{3}{2} \cdot 3x - \frac{3}{2} \cdot 4 \][/tex]
[tex]\[ y = \frac{3}{2}x^2 - \frac{9}{2}x - 6 \][/tex]

Now we can write the quadratic equation:
[tex]\[ y = 1.5x^2 - 4.5x - 6 \][/tex]

### Conclusion
The standard form of the quadratic equation that satisfies these conditions is:
[tex]\[ y = 1.5x^2 - 4.5x - 6 \][/tex]

Comparing this with the given options:
[tex]\[ \boxed{y = 1.5 x^2 - 4.5 x - 6} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.